Supremasi Injil Berdasarkan Surat Galatia 1:1-10 - Masye Rompa (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2020)
Abstract: There’s no other Gospel! There is only one Gospel! Understanding the Gospel that it has the highest value brings the church to put the Gospel as the center of it. It’s not just knowing about the Gospel, but makes it being carved, planted, and rooted in the life of believer. The problem is the supremacy of the Gospel is not clear enough in the church, nor any organizations now. Finally, there are a lot of teachings that enter into the church and try to destroy the authority of the Bible and change its core. If it’s so, how the church will be? Looking at that phenomenon, we must go back to what the Bible says about the Gospel. Specifically in this journal, the writer explains about the supremacy of the Gospel based on Galatians 1:1-10.